Guidance and control methodologies for marine vehicles: A survey - Karimi, Hamid Reza; Lu, Yanyang (Control engineering practice, 2021)
Offshore mechatronics systems engineering has recently received high attentions in various sectors such as energy, transportation, etc. Specifically, offshore robotic vehicles have become challenging topics in terms of design, guidance, control and maintenance aspects. Based on these reasons, in this article, some recent developments on the guidance and control methodologies for marine robotic vehicles are surveyed. The application-oriented methodologies under consideration mainly include fuzzy-based control design approach, neural network-based control design scheme, dynamic surface control strategy, feedback control technique as well as sliding model control method, for instance. With the help of these methodologies, the developments on various guidance and robust control issues are reviewed in great detail. In practical engineering, guidance and control design problems are mainly addressed for the maneuvering, path following, trajectory tracking, formation control and consensus. In particular, the state of art of the solution to guidance and control issues for marine robotic vehicles under different control methodologies is addressed respectively. Finally, some latest research results in filtering and control design developments are introduced, some conclusions are drawn and several possible future research directions based on the latest results are pointed out.